Civamide Nasal Spray: A Breath of Fresh Air in Migraine and Cluster Headache Therapy? Insights from A Systematic Review - Cyntia Arum; Danar Dwi Anandhika; Nabil Hajar; Moh. Iqbal Setiawan; Fatima Khiarun Nisa; Suwandhi; Firza Yoga Baskoro; Hera Dwi Priharti (Magna Neurologica, 2026)
Background: Migraines and cluster headaches are severe neurological disorders characterized by complex pathophysiological mechanisms, particularly involving the trigeminal nerve and vascular inflammatory responses. Both conditions primarily affect the trigeminal nerve, a key pathway in pain transmission, and are closely associated with vascular inflammation. Migraines are typically characterized by recurrent, unilateral, and intense headaches, whereas cluster headaches are marked by excruciating pain, often localized around the eye. These disorders are multifactorial, with various mechanisms contributing to their initiation and persistence. Civamide nasal spray, which modulates neural pathways, has emerged as a promising therapeutic option for targeted pain relief. This study aims to evaluate the effectiveness of Civamide nasal spray in managing these debilitating headaches. Objective: To assess the efficacy of civamide nasal spray in treating migraine and cluster headache attacks. Methods: This study followed the Synthesis without Meta-analysis (SWiM) guideline. A systematic search was conducted using a predefined query in Medline, Google Scholar, and Cochrane Central Library. Eight independent reviewers screened studies for eligibility based inclusion criteria and assessed the risk of bias using the Cochrane RoB 2.0 tool. Results: Two eligible studies were analyzed. Participants receiving civamide demonstrated a greater reduction in weekly headache frequency compared with those receiving a placebo. Additionally, civamide treatment was associated with decrease in pain intensity. Conclusion: The findings suggest that civamide nasal spray effectively reduces both the frequency and severity of headaches. Nonetheless, further investigations, particularly evaluating its long-term preventive use, are required to establish its clinical role in migraine and cluster headache management.